Chemical pipeline lining anticorrosive coating and preparation method thereof
By adopting the synergistic effect of silicone modified epoxy resin and inorganic silicone hybrid epoxy resin in the anti-corrosion coating for chemical industry, as well as the core-shell structure modified fly ash and three-roll rolling grinding process, the problem of insufficient anti-corrosion performance and adhesion of the existing coating in extreme chemical environments is solved, and the coating has been greatly improved in chemical resistance, high temperature resistance and adhesion.
Patent Information
- Application Number
- CN202510342457.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-21
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2045-03-21
AI Technical Summary
The existing anti-corrosion coatings for chemical industry show insufficient anti-corrosion and adhesion in extreme chemical environments, resulting in problems such as coating peeling, blistering, cracking, etc., affecting the long-term stable operation and safety performance of the pipeline.
The synergistic effect of silicone modified epoxy resin and inorganic silicone hybrid epoxy resin is adopted, combined with core-shell structure modified fly ash and three-roll grinding process, an anticorrosion coating with excellent chemical resistance, high temperature resistance and adhesion is prepared.
It significantly improves the adhesion and corrosion resistance of the coating, extends the service life of the coating, reduces maintenance costs, and is suitable for a variety of extreme chemical environments.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of chemical anti-corrosion, and specifically relates to a method for preparing an anti-corrosion coating for a pipeline lining used in the chemical industry. Background Art
[0002] With the rapid development of the chemical industry, anti-corrosion coated pipelines play a vital role in the chemical production process and are widely used in the transportation of media such as oil, natural gas, and chemical raw materials. However, the existing anti-corrosion coated pipelines have exposed many problems in practical applications, especially in some special chemical environments, where their performance is difficult to meet increasingly stringent requirements. Although there are already a variety of anti-corrosion coated pipeline products on the market, which can provide anti-corrosion protection to a certain extent, the anti-corrosion performance and adhesion of these coatings are often insufficient under some extreme chemical environments, such as strong acids, strong alkalis, high temperatures, high salt spray and other complex working conditions. This causes the coating to easily fall off, bubble, crack, etc., which in turn causes the pipeline to lose its anti-corrosion protection, affecting its long-term stable operation and safety performance, and increasing the risks and maintenance costs in the chemical production process.
[0003] In order to solve the above problems, some attempts have been made in the industry, such as improving the anti-corrosion effect by improving coating materials and coating processes. However, these methods still have limitations in practical applications. On the one hand, although some coating materials have improved chemical resistance and high temperature resistance to a certain extent, their preparation process is complicated and the cost is high, which is not conducive to large-scale industrial production and application. On the other hand, although some coating processes can improve the adhesion of the coating, the operation is cumbersome and the construction is difficult, which increases production time and labor costs.
[0004] The patent document with publication number CN111828777B discloses a pipeline anti-corrosion coating processing method, which adopts the method of wrapping a stainless steel coil with a topcoat sprayed on the outer side on a cast iron pipe and fixing it with a barrier adhesive. Although this method improves the anti-corrosion effect and work efficiency to a certain extent, since the stainless steel coil is pre-sprayed with topcoat, the topcoat is easily damaged during storage and transportation, thereby affecting the final anti-corrosion performance. In addition, the process of wrapping and fixing the stainless steel coil is relatively complicated, which not only increases the difficulty of construction, but also leads to increased costs.
[0005] Patent document with publication number CN107629514A discloses an anti-corrosion coating for oil pipelines, which is composed of multiple raw materials such as epoxy resin, clamshell powder, polytetrafluoroethylene, etc. Although the coating has good high temperature resistance and oxidation resistance, it is not conducive to large-scale industrial production and application due to its complex components, cumbersome preparation process and high cost. At the same time, in some extreme chemical environments, such as strong acid and alkali and salt spray environments, its corrosion resistance still needs to be further improved.
[0006] In addition, the patent document with publication number CN118066406B discloses an oil and gas pipeline with an anti-corrosion coating, which adopts a double-layer epoxy resin anti-corrosion coating set inside the pipeline, and transfers heat to the outer pipeline surface through a heat conduction mechanism to quickly evaporate the attached liquid. Although this method can effectively improve the corrosion resistance of the pipeline, its structure is complicated, and the setting of the heat conduction mechanism increases the manufacturing cost. In addition, in some special environments, uneven heat transfer may cause aging and failure of the coating.
[0007] In summary, the anti-corrosion coating pipelines currently on the market are difficult to effectively respond to the new requirements for anti-corrosion performance, adhesion and cost control under complex working conditions. Therefore, the present invention provides a method for preparing an anti-corrosion coating for the inner lining of a chemical pipeline, aiming to overcome the above-mentioned deficiencies in the prior art, by optimizing the coating material and coating process, improving the chemical resistance and high temperature resistance of the coating, simplifying the construction steps, and reducing the production cost, so as to meet the demand for high-quality anti-corrosion coatings for modern chemical pipelines, and provide more reliable technical guarantees for the safe production and stable operation of the chemical industry. Summary of the invention
[0008] The purpose of the present invention is to provide a method for preparing an anti-corrosion coating for the lining of chemical pipelines. The coating prepared by the method has excellent chemical resistance, high temperature resistance and adhesion, and is suitable for a variety of extreme chemical environments. At the same time, the preparation process is simple, the cost is low, and it is suitable for large-scale industrial production and application.
[0009] To achieve the above object, the technical solution adopted by the present invention is: The primer contains the following components: 15-25 parts of organosilicon-modified epoxy resin, 5-15 parts of inorganic silicon hybrid epoxy resin, 20-30 parts of zinc phosphate antirust pigment, 10-20 parts of modified fly ash, 30-40 parts of body filler, and 8-12 parts of curing agent; The topcoat comprises the following components: 35-45 parts of fluorocarbon modified epoxy resin, 15-20 parts of KH-560 modified silicon carbide, 8-12 parts of molybdenum disulfide, 5-8 parts of isocyanate prepolymer and 10-15 parts of rutile titanium dioxide.
[0010] The modified fly ash is specifically a dense shielded core-shell composite coated with fly ash titanium dioxide.
[0011] Specifically, the preparation of the dense shielded core-shell composite comprises the following steps: 1) Weigh tetrabutyl titanate and fly ash in a mass ratio of 0.3-0.5:1, mix tetrabutyl titanate and anhydrous ethanol in a mass ratio of 1:3, add 0.5% hydrochloric acid aqueous solution, the volume ratio of ethanol to water in the solution is 4:1, and then hydrolyze for 30 minutes at a pH of 1.5-2 and a temperature of 25-30°C; 2) adding fly ash and ultrasonically dispersing it at 35-45 kHz and 250-350 W for 20-40 min. After completion, centrifugation is performed at a speed of 3500-4500 rpm, a time of 10-20 minutes, and a temperature of 50-70° C., and then transferred to a vacuum box and vacuum dried at 60° C. for 2 hours to obtain a dense shielded core-shell composite.
[0012] Specifically, the curing agent is compounded by polyetheramine D230 / D400 and alicyclic amine Ancamine2280 in a mass ratio of 4:1.
[0013] Specifically, the physical filler is composed of talcum powder, barite powder and mica powder in a mass ratio of 5:4:1, the zinc phosphate anti-rust pigment is modified by silane coupling agent KH-570, the amount of modifier added is 1% to 2% of the mass of zinc phosphate, and the mass ratio of the modified fly ash to the physical filler is 1:2 to 3.
[0014] Specifically, the fluorocarbon modified epoxy resin is a tetrafluoroethylene-vinyl ether copolymer, the fluorine content is ≥55%, the isocyanate prepolymer is hexamethylene diisocyanate biuret or isophorone diisocyanate trimer, and the molar ratio of the isocyanate prepolymer to the fluorocarbon modified epoxy resin is 1:1.2-1.5. The molar ratio of tetrafluoroethylene to vinyl ether is 1:0.8-1.2.
[0015] Specifically, the dry film thickness of the primer layer is 200-300 μm, the dry film thickness of the topcoat layer is 150-250 μm, and the total dry film thickness is 350-550 μm.
[0016] A method for preparing an anti-corrosion coating for a chemical pipeline lining comprises the following steps: Primer preparation: a) Firstly, the organosilicon-modified epoxy resin, the inorganic silicon hybrid epoxy resin, the KH-570 modified zinc phosphate, the modified fly ash and the physical filler are mixed according to the proportion; b) Disperse at 2000±50rpm for 60min under nitrogen protection, add the curing agent prepared by polyetheramine D230 / D400 and Ancamine2280 in a mass ratio of 4:1, and continue dispersing at 500±50rpm for 30min. Curing at 25℃ for 30min, then apply the mixture to the surface of the substrate and cure in an oven at 80℃ for 1 hour to form a primer layer.
[0017] Topcoat preparation: c) Mix fluorocarbon modified epoxy resin, KH-560 modified silicon carbide, molybdenum disulfide, isocyanate prepolymer and rutile titanium dioxide according to the proportion, pre-react at a temperature controlled at 60±2℃ for 1 hour, and grind for 3 times on a three-roll mill at a speed of 0.4-0.6MPa and 1.5-2.0m / s to a fineness of ≤45μm. Finally, apply the topcoat on the primer layer and cure it at 60℃ for 4 hours to form a topcoat layer.
[0018] Specifically, in step c), when the rolling pressure of the three-roll mill is 0.6 MPa, the median particle size D50 of the silicon carbide particles is ≤20 μm.
[0019] The structural composition, implementation mode and operating principle of the present invention are as follows: 1. Synergistic effect of organic / inorganic silicon hybrid epoxy resin: The flexible chain segments of organic silicon modified epoxy resin and the nano-SiO 2 The network forms an interpenetrating structure, which enhances the adhesion of the coating.
[0020] 2. Sealing effect of core-shell structure modified fly ash: TiO 2 The coating layer reduces the porosity to ≤1.5%, blocking the penetration of corrosive media.
[0021] 3. Optimized preparation process: The present invention ensures uniform mixing and sufficient reaction of each component through step-by-step dispersion, pre-reaction and milling processes. In particular, the optimized parameters of the three-roll mill (roller pressure, milling times and line speed) and the directional dispersion of the roll milling process: the silicon carbide particles are refined and work together with molybdenum disulfide to improve wear resistance, so that the fineness of the coating is optimized, the smoothness and density of the coating are improved, and thus the anti-corrosion effect and adhesion are enhanced.
[0022] The beneficial effects of the present invention are as follows: 1. Surface modification using epoxy silane coupling agent significantly improves the adhesion and chemical resistance of the coating. The modified resin forms a dense cross-linked network in the coating, effectively preventing the penetration of corrosive media.
[0023] 2. Enhanced adhesion and mechanical strength: The synergistic effect of the primer layer and the topcoat layer and the use of modified anti-rust fillers significantly improve the adhesion and mechanical strength between the coating and the substrate, extend the service life of the coating and reduce maintenance costs.
[0024] 3. Optimized preparation process: The present invention ensures uniform mixing and sufficient reaction of each component through step-by-step dispersion, pre-reaction and milling processes. In particular, the optimized parameters of the three-roll mill (roller pressure, milling times and line speed) make the fineness of the coating optimal, improve the smoothness and density of the coating, and thus enhance the anti-corrosion effect and adhesion. DETAILED DESCRIPTION
[0025] The present invention is further described below in conjunction with specific embodiments, but the present invention is not limited to these embodiments. Those skilled in the art should recognize that the present invention covers all possible alternatives, improvements and equivalents within the scope of the claims.
[0026] The following examples were tested according to the following experimental scheme, and the following are the experimental conditions of all examples: The physical filler is composed of talcum powder, barite powder and mica powder in a mass ratio of 5:4:1.
[0027] The inorganic silicon hybrid epoxy resin is prepared by a sol-gel method, and the specific steps are as follows: (1) Mix ethyl orthosilicate and anhydrous ethanol in a mass ratio of 1:4, add 0.1 mol / L hydrochloric acid to adjust the pH to 3, and hydrolyze for 30 minutes to generate SiO 2 Sol; (2) Epoxy resin E-51 and SiO 2 The sols were mixed in a mass ratio of 10:1 and stirred at 60°C for 2 hours to form an inorganic silicon hybrid epoxy resin, in which SiO 2 The particle size of nanoparticles is 20-50nm.
[0028] Example 1
[0029] Preparation of modified fly ash: first, weigh tetrabutyl titanate and fly ash at a mass ratio of 0.4:1, mix tetrabutyl titanate and anhydrous ethanol at a ratio of 1:3, pour in 0.5% dilute hydrochloric acid water, in which the volume ratio of ethanol to water is 4:1, and the pH value is adjusted to 1.8, and stir and hydrolyze at 30°C for 30 minutes to obtain a transparent sol; then add fly ash and treat it with a 40kHz ultrasonic machine (power 300 watts) for 30 minutes to allow titanium dioxide to evenly coat the surface of the fly ash; then use a centrifuge at 4000 rpm for 15 minutes to remove excess liquid, and then put it in a 60°C vacuum oven for 2 hours to obtain a dry core-shell fly ash with a porosity of ≤0.5%.
[0030] Preparation of primer: 20 parts of organosilicon-modified epoxy resin, 10 parts of inorganic silicon hybrid epoxy resin, 25 parts of silane-modified zinc phosphate, 15 parts of modified fly ash, and 35 parts of a physical filler mixed with talcum powder, barite powder and mica powder in a ratio of 5:4:1 are weighed by weight, and stirred at a high speed of 2000 rpm for 1 hour under nitrogen protection until the mixed liquid is like thick yogurt; then 10 parts of a curing agent mixed with polyetheramine D400 and alicyclic amine Ancamine2280 in a ratio of 4:1 is added, the speed is reduced to 500 rpm and stirring is continued for 30 minutes, and then it is allowed to stand for 30 minutes to defoam; finally, it is applied to the inner wall of the steel pipe with a spray gun, and baked at 80°C for 1 hour to form a primer layer 200-300 microns thick.
[0031] Preparation of topcoat: weigh 40 parts of fluorocarbon resin, 18 parts of KH-560 modified silicon carbide, 10 parts of molybdenum disulfide, 6 parts of hexamethylene diisocyanate biuret, and 12 parts of titanium dioxide, then mix and heat to 60°C for pre-reaction for 1 hour to allow the materials to initially bond; then use a three-roll mill with a pressure of 0.5MPa and a line speed of 1.8m / s to repeatedly roll 3 times to grind the particles to ≤45 microns; finally apply it on the primer and bake at 60°C for 4 hours to form a topcoat layer of 150~250 microns, of which the total thickness of the topcoat and primer is 350~550 microns.
[0032] Example 2
[0033] Primer: 25 parts of organosilicon-modified epoxy resin, 5 parts of inorganic silicon hybrid epoxy resin, and 20 parts of modified fly ash.
[0034] Topcoat: 45 parts of fluorocarbon modified epoxy resin and 8 parts of isophorone diisocyanate trimer, wherein the molar ratio of isophorone diisocyanate trimer to fluorocarbon resin is 1:1.5.
[0035] In addition, during the preparation of the modified fly ash, the pH of the hydrolysis was 1.5, the ultrasonic dispersion was performed at a frequency of 45 kHz, a power of 350 W, and a running time of 40 min, while the centrifugal separation was performed at 4500 rpm for 20 min, and the rest was the same as in Example 1.
[0036] Example 3
[0037] Primer: 15 parts of silicone modified epoxy resin and 40 parts of body filler.
[0038] Topcoat: 35 parts of fluorocarbon modified epoxy resin, 10 parts of rutile titanium dioxide, and the rest are the same as in Example 1.
[0039] Example 4
[0040] Topcoat: The NCO content of hexamethylene diisocyanate biuret is 22%, the three-roll mill pressure is 0.6 MPa, the line speed is 2.0 m / s, and the rest is the same as in Example 1.
[0041] Example 5
[0042] Primer: Curing time is shortened to 15 minutes.
[0043] Topcoat: pre-reaction temperature 62°C, curing time compressed to 3h, and the rest is the same as Example 1.
[0044] Comparative Example 1 Primer: Use original fly ash without titanium dioxide coating (unmodified fly ash), and the rest is the same as Example 1.
[0045] Comparative Example 2 Primer: The resin is ordinary epoxy resin E-51, and the rest is the same as in Example 1.
[0046] Comparative Example 3 The three-roll mill step was omitted during the preparation process, and the mixing and coating were performed directly. The rest was the same as in Example 1.
[0047] Adhesion (MPa) Salt spray resistance time (h) Taber wear (g / 1000 times) Porosity (%) Hydrochloric acid resistance time (h) Topcoat dry film thickness (μm) Primer dry grinding thickness (μm) Example 1 18 (cohesive fracture) 2965 (Rust < 0.1%) 0.021 ≤1.3 720 (no foaming) 200 250 Example 2 16 (cohesive fracture) 2896 (rust-free) 0.024 ≤1.5 684 (no foaming) 200 200 Example 3 14 (cohesive fracture) 2637 (Rust < 0.5%) 0.031 ≤1.7 572 (slightly bubbling) 150 300 Example 4 17 (cohesive fracture) 2564 (Rust < 0.2%) 0.037 ≤1.8 531 (no foaming) 250 200 Example 5 15 (cohesive fracture) 2342 (Rust < 0.5%) 0.038 ≤1.9 519 (Blistering Edges) 250 300 Comparative Example 1 8 (cohesive fracture) 814 (Rust > 50%) 0.056 5.2 263 (large area of blistering) 200 250 Comparative Example 2 10 (cohesive fracture) 1239 (Rust ≈ 20%) 0.077 2.0 121 (local blistering) 200 250 Comparative Example 3 6 (cohesive fracture) 1764 (Rust ≈ 10%) 0.089 2.3 364 (edge blistering) 200 250
[0048] Table 1 Test data According to the comparison between Example 1 and Comparative Example 1, the core-shell structure reduces the porosity by 90% and increases the salt spray resistance time by 300%.
[0049] The following is a test method for a specific embodiment: 1. Adhesion test A hydraulic puller (Elcometer506) was used to adhere a 20 mm diameter forging die to the coating surface. The glue was cured for 24 hours, and then a vertical tensile force was applied until the coating fell off. The maximum tensile force (MPa) was recorded, and the fracture type (cohesive / interface / glue failure) was observed. Each sample was repeated 3 times and the average value was taken.
[0050] 2. Salt spray resistance test The coating samples were placed in a salt spray chamber to simulate the marine environment (5% NaCl solution, 35°C). The rusted area was checked every 24 hours and the time (hours) when rust first appeared was recorded. The test was then conducted until the coating completely failed or the upper limit of 4000 hours was reached.
[0051] 3. Wear resistance test Using a Taber abraser, load a CS-10 grinding wheel (load 1 kg), rotate the sample 1000 times, weigh the coating weight loss (g / 1000 times), and observe whether the coating is worn to the substrate.
[0052] 4. Porosity test The coating porosity was measured by mercury intrusion porosimetry according to ASTM D4404-18 standard using an AutoPore V9600 mercury intrusion porosimeter with a pressure range of 0.1-60000 psi, and the sealing effect of the core-shell composite on the pores was analyzed. The pore distribution of the unmodified fly ash (Comparative Example 1) and the modified fly ash (Example 1) was then compared.
[0053] 5. Chemical resistance test The coating was immersed in 10% hydrochloric acid solution (25°C), and the blistering or shedding was observed every 24 hours, and the coating failure time (hours) was recorded.
[0054] The present invention achieves a breakthrough improvement in coating performance through the synergistic enhancement effect of organic / inorganic hybrid epoxy resin, the hermetic sealing effect of core-shell structure modified fly ash, and the directional dispersion technology of three-roll milling process. The adhesion of Example 1 reaches 18MPa (125% higher than the 8MPa of the traditional coating), which is attributed to the flexible chain segment of the organosilicon modified epoxy resin and the nano-SiO 2 The network synergistically strengthens the interface bonding, and the curing agent ratio (polyetheramine D400: alicyclic amine = 4:1) optimizes the crosslinking density; Example 2 has a salt spray resistance of 2896 hours (compared with 800 hours of unmodified fly ash, an increase of about 256%). 2 The coating layer (hydrolysis pH=1.5) reduces the fly ash porosity to ≤1.5%, effectively blocking the chloride ion penetration path, and the high-fluorine content resin forms a continuous shielding layer; this is due to the "hard support-lubrication and drag reduction" synergistic mechanism of the directional arrangement of molybdenum disulfide flakes (friction coefficient ≤0.12) under the high pressure of 0.6MPa on the three-roll mill and the refinement of silicon carbide particles.
[0055] In addition to the above embodiments, the present invention may also have other implementation modes. Any technical solution formed by equivalent replacement or equivalent transformation falls within the protection scope required by the present invention.
Claims
1. A chemical pipeline lining anti-corrosion coating, characterized in that: It is composed of primer and topcoat, by weight: The primer contains the following components: 15-25 parts of organosilicon-modified epoxy resin, 5-15 parts of inorganic silicon hybrid epoxy resin, 20-30 parts of zinc phosphate antirust pigment, 10-20 parts of modified fly ash, 30-40 parts of body filler, and 8-12 parts of curing agent; The topcoat comprises the following components: 35-45 parts of fluorocarbon modified epoxy resin, 15-20 parts of KH-560 modified silicon carbide, 8-12 parts of molybdenum disulfide, 5-8 parts of isocyanate prepolymer, and 10-15 parts of rutile titanium dioxide; The modified fly ash is specifically a dense shielded core-shell composite coated with fly ash titanium dioxide; The physical filler is composed of talcum powder, barite powder and mica powder in a mass ratio of 5:4:
1.
2. The anti-corrosion coating for chemical pipeline lining according to claim 1, characterized in that: The preparation of the dense shielded core-shell composite comprises the following steps: 1) Weigh tetrabutyl titanate and fly ash in a mass ratio of 0.3-0.5:1, mix tetrabutyl titanate and anhydrous ethanol in a mass ratio of 1:3, add 0.5% hydrochloric acid aqueous solution, the volume ratio of ethanol to water in the solution is 4:1, and then hydrolyze for 30 minutes at a pH of 1.5-2 and a temperature of 25-30°C; 2) adding fly ash and ultrasonically dispersing it at 35-45 kHz and 250-350 W for 20-40 min. After completion, centrifugation is performed at a speed of 3500-4500 rpm, a time of 10-20 minutes, and a temperature of 50-70° C., and then transferred to a vacuum box and vacuum dried at 60° C. for 2 hours to obtain a dense shielded core-shell composite.
3. The anti-corrosion coating for chemical pipeline lining according to claim 1, characterized in that: The curing agent is compounded by polyetheramine D230 / D400 and alicyclic amine Ancamine2280 in a mass ratio of 4:
1.
4. The anti-corrosion coating for chemical pipeline lining according to claim 1, characterized in that: The zinc phosphate antirust pigment is modified by a silane coupling agent KH-570, the amount of the modifier added is 1% to 2% of the mass of the zinc phosphate, and the mass ratio of the modified fly ash to the body filler is 1:2 to 3.
5. The anti-corrosion coating for chemical pipeline lining according to claim 1, characterized in that: The fluorocarbon modified epoxy resin is a tetrafluoroethylene-vinyl ether copolymer with a fluorine content of ≥55%. The isocyanate prepolymer is hexamethylene diisocyanate biuret or isophorone diisocyanate trimer, and the molar ratio of the isocyanate prepolymer to the fluorocarbon modified epoxy resin is 1:1.2-1.
5.
6. The anti-corrosion coating for chemical pipeline lining according to claim 1, characterized in that: The dry film thickness of the primer layer is 200-300 μm, the dry film thickness of the topcoat layer is 150-250 μm, and the total dry film thickness is 350-550 μm.
7. A method for preparing an anti-corrosion coating for chemical pipeline lining according to any one of claims 1 to 6, characterized in that The following steps are involved: Primer preparation: a) Firstly, the organosilicon-modified epoxy resin, the inorganic silicon hybrid epoxy resin, the KH-570 modified zinc phosphate, the modified fly ash and the physical filler are mixed according to the proportion; b) Disperse at 2000±50rpm for 60min under nitrogen protection, add a curing agent prepared by polyetheramine D230 / D400 and Ancamine2280 in a mass ratio of 4:1, continue dispersing at 500±50rpm for 30min, mature at 25℃ for 30min, then apply the mixture on the surface of the substrate, and place it in an oven at 80℃ for curing for 1 hour to form a primer layer; Topcoat preparation: c) Mix fluorocarbon modified epoxy resin, KH-560 modified silicon carbide, molybdenum disulfide, isocyanate prepolymer and rutile titanium dioxide according to the proportion, pre-react at a temperature controlled at 60±2℃ for 1 hour, and grind for 3 times on a three-roll mill at a speed of 0.4-0.6MPa and 1.5-2.0m / s to a fineness of ≤45μm. Finally, apply the topcoat on the primer layer and cure it at 60℃ for 4 hours to form a topcoat layer.
Citation Information
Patent Citations
Anticorrosive coating for petroleum transmission pipeline
CN107629514A
Pipeline anti-corrosion coating processing method
CN111828777B
Oil and gas transmission pipeline with anti-corrosion coating
CN118066406B
Nano zinc aluminum modified epoxy-fluorocarbon coating
CN101007922A
Pipeline inner wall anticorrosive paint and preparation method thereof
CN117701109A